Nightglow imaging of different types of events, including a mesospheric bore observed on the night of February 15, 2007 from Tirunelveli (8.7°N) - Narayanan, V. Lakshmi; Gurubaran, S.; Emperumal, K. (My University, 2012)
All-sky imaging observations on the night of February 15, 2007, from Tirunelveli (8.7°N), revealed a variety of short-period small-scale dynamical features comprising of atmospheric gravity waves, ripples and a mesospheric bore. A total of 11 wave events other than the convective ripple patches were identified. All the ripple features of wavelengths less than 10 km were found to propagate nearly in the same direction and they were frequent in the early part of the night. The presence of a dynamical ripple in all-sky images was also inferred. One of the identified events displayed steepening of the leading front and subsequent evolution into a mesospheric bore. Apart from these events, there were several ‘quasi-coherent’ features that were not clearly discernable for deduction of propagation velocities or wavelengths. In order to have a better understanding of these events, we used winds measured by co-located MF radar to derive intrinsic wave parameters. The MF radar winds and average of zenith intensity values from the imager indicate the presence of medium frequency waves of time periods in the range 0.75–3 h. In addition, two sets of temperature measurements made by SABER instrument onboard TIMED mission were also used. The temperature profiles implied strong tidal control on this night. An attempt was also made to infer the source of the wave activity observed at mesospheric altitudes and the effects of wind filtering at altitudes below nightglow emission altitudes.
Keywords: Quasi-monochromatic gravity waves; Ripples; Mesospheric bores; Thermal and Doppler ducts; Tirunelveli